نوجوانوں میں خود اعتمادی کے فروغ کا نبوی منہج: The Prophetic Method of Increasing Self Confidence in Youth (Al-Aasar, 2025)
It is an undeniable fact that youth plays the role of backbone in the success and survival of any society or movement. On the other hand, the misguided behaviour of this group proofs to be a major cause of social destruction. Therefore, in order to guide this group correctly, knowledge of their understanding and psychological requirements with the art of utilizing their best abilities can lead society on the path to a successful and prosperous life. At this stage of their lives youngsters must be eager to show the essence of their immense powers, they like to achieve their goal through hardships. They not only imagine their abilities like conqueror of the world but also they create stories of their victory and success. They want to be accepted their opinion, appreciation and respect from society. Accepting their opinion with appropriate guidance and support not only boosts their morale and ensure their success but also enhances their self-confidence and ability to lead successful life. In appropriately rejecting their opinions and diminishing their importance not only creates many psychological problems for them but also destabilize the social system and make tragic events as a part of history. In this research article we will examine the results and the effectiveness of the acceptance the opinions of youth and its importance in social sector in the light of Seerah of the prophet Muhammed ﷺ in narrative and qualitative manner.